2001
DOI: 10.1034/j.1600-0846.2001.70206.x
|View full text |Cite
|
Sign up to set email alerts
|

Females have lower skin surface pH than men

Abstract: Spontaneous skin surface pH was found to be significantly lower in women, as compared to men--albeit, the difference was small and of unknown relevance. Nevertheless, comparative studies on skin surface pH should be balanced with respect to gender. There appeared to be no right/left difference and no systematic change during the working day. Also, measurements should not be conducted close to the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 5 publications
7
60
3
2
Order By: Relevance
“…The pH value was higher in women (5.6 ± 0.4) than in men (4.3 ± 0.4) (see table 1). Similar gender-related differences in pH have been reported by other groups [10, 11], in contrast to reversed results [12 ]and no differences [9]. Differences in cosmetic habits that can cause an increase in pH [21] are proposed as the reason for such conflicting results [28.]…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The pH value was higher in women (5.6 ± 0.4) than in men (4.3 ± 0.4) (see table 1). Similar gender-related differences in pH have been reported by other groups [10, 11], in contrast to reversed results [12 ]and no differences [9]. Differences in cosmetic habits that can cause an increase in pH [21] are proposed as the reason for such conflicting results [28.]…”
Section: Discussioncontrasting
confidence: 49%
“…In other studies, women had higher pH levels than men [10, 11,] while another group reported a lower skin surface pH in women than in men [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The skin pH then appears to remain constant until approximately 80 years of age. Regarding gender, a few reports have indicated gender associations [16][17][18], but these are not supported by other studies [12,19,20]. In our study, the initial skin pH before using the product was 4.8, the same as the average reported skin pH in humans.…”
Section: Discussionsupporting
confidence: 49%
“…In other words, pH could be one of the factors that determine locale-specific gene expression patterns, since certain body sites are characterized by variations in pH from the homeostatic 7.4 ( Fig. 6) (5,10,16,21,22,31,41,53). Given the breadth of the MAS, plus the fact that the intracellular pH is maintained within very narrow limits, the pH differential must be sensed by one or more surface receptors and transduced to the interior of the cell.…”
Section: Discussionmentioning
confidence: 99%